Therapeutic Communication in Enhancing Pregnant Women’s Trust in Antenatal Care - Panjarwanto, Dwi Andhika; Ernungtyas, Niken Febrina; Indrawan, I Wayan Agung (Riviera Publishing, 2025)
This study aims to analyze the role of therapeutic communication in increasing pregnant women's trust in antenatal care (ANC) services at Patut Patuh Patju Hospital, West Lombok Regency. The research method used is qualitative with a descriptive-analytical approach through in-depth interviews, participatory observation, and documentation. The results of the study showed that therapeutic communication of medical personnel was carried out using simple language, empathetic attitudes, two-way communication, friendly approaches, and emotional support. These factors have been shown to be effective in creating comfort, reducing anxiety, and strengthening the active involvement of pregnant women in health checkups. In addition, support from family, peer groups, and sensitivity to local culture also strengthened pregnant women's trust in medical services. This study confirms that therapeutic communication is not only a medium for delivering medical information but also an important strategy in building a relationship of mutual trust that contributes to the compliance of pregnant women undergoing ANC examinations. These findings are expected to serve as a reference for health workers and policymakers in improving the quality of antenatal services based on empathic communication, trust, and social support.